ANALISA DAN PERANCANGAN SISTEM INFORMASI SEKOLAH BERBASIS WEB DI SMA 2 KOTA SERANG - Beny Suhendar (Jurnal Sistem Informasi dan Informatika (Simika), 2018)
This research entitled "Web Based Information Sistem at Serang High School (Senior High School) of Serang Regency for the data processing of school in Serang Regency/City through Education Office This sistem is designed using UML Modeling, while programming language used is PHP and MYSQL database. The result of this design is the information sistem application that presents information owned by each Secondary School in Serang Regency/City so that prospective students, parents, and community can find the school information through Education Office of Serang Regency / City